Severe skin toxicity during whole-brain radiotherapy, targeted therapy, and additional drug intake including St. John’s wort skin oil - Eichkorn, Tanja; Schunn, Fabian; Regnery, Sebastian; El-Shafie, Rami; Hörner-Rieber, Juliane; Adeberg, Sebastian; Herfarth, Klaus; Debus, Jürgen; König, Laila (Strahlentherapie und Onkologie, 2021)
Metastatic non-small cell lung cancer (NSCLC) often requires a multimodal treatment including chemotherapy, targeted therapy and radiotherapy. In addition to this, many patients take supportive drugs. Since only scarce data on possible interactions between radiotherapy and pharmaceutical or herbal drugs exist, description of clinical cases is of special interest.